Peran Keluarga terhadap Prestasi Mahasiswa/i Program Studi Pendidikan Bahasa Inggris, Universitas Victory Sorong - Leuwol , Natasya Virginia; Zalzabila, Fauzi; Salay, Rita; Bonggoibo, Ersiana; Hosyo, Yustina; Kelmaskosu, Royan (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to determine the role of family in influencing the achievement of students of English education study program. This research uses descriptive qualitative research method with data analysis techniques conducted in-depth and interpretative. The results showed that the role of family has a significant influence on the achievement of students of English education study program. Family as the first environment owned by students is very influential in developing learning achievement through proper education and good communication between family members. This result is in line with previous research which also found that the role of family has a significant influence on student achievement (Kurniawan, 2018; Suryadi, 2019). In this study, data were collected through structured and non-structured interviews with 20 respondents consisting of parents of students and students of the English education study program. The results showed that the role of the family in developing students' learning achievement through proper education and good communication between family members. The results also show that the role of the family is very important in developing students' English language skills. This research has significant practical implications in improving student achievement in the English education study program. In practice, this study shows that the role of the family must be considered in the educational process, so as to improve student achievement. Therefore, this research is expected to be a reference for educators and parents in improving student achievement in the English education study program.